Funding the IMF. (Pamphlet Series; Pamphlet Series, No., 2005)
This paper discusses reasons functions of the IMF, why it needs more resources, and how these resources will be used. The IMF provides a forum for cooperation, having as its objective the balanced expansion of international trade in order to stimulate employment and improve economic conditions in its member countries. In its relations with its members, the IMF seeks to promote sound policies through advice as well as by providing technical assistance in many fields. The IMF has facilitated negotiations between debtors and creditors on the types and terms of financing agreements. It has also participated in the debt-restructuring agreements with commercial banks. The restoration of growth in developing countries is essential not only for the sake of the well-being of these countries but also in the interest of the global community. Thus, the IMF must be responsive in meeting the needs of all its members, not solely those in crisis situations. Good economic management is all-important and for this to be effective, however, it must be supported by adequate financing.